Exploring Klebsiella pneumoniae in Healthy Poultry Reveals High Genetic Diversity, Good Biofilm-Forming Abilities and Higher Prevalence in Turkeys Than Broilers - Franklin-Alming, Fiona V.; Kaspersen, Håkon; Hetland, Marit A. K.; Bakksjø, Ragna-Johanne; Nesse, Live L.; Leangapichart, Thongpan; Löhr, Iren H.; Telke, Amar A.; Sunde, Marianne (Frontiers in Microbiology, 2021)
Klebsiella pneumoniae is a well-studied human pathogen for which antimicrobial resistant and hypervirulent clones have emerged globally. K. pneumoniae is also present in a variety of environmental niches, but currently there is a lack of knowledge on the occurrence and characteristics of K. pneumoniae from non-human sources. Certain environmental niches, e.g. animals, may be associated with high K. pneumoniae abundance, and these can constitute a reservoir for further transmission of strains and genetic elements. The aim of this study was to explore and characterize K. pneumoniae from healthy broilers and turkeys. A total of 511 cecal samples (broiler n = 356, turkey n = 155), included in the Norwegian monitoring program for antimicrobial resistance (AMR) in the veterinary sector (NORM-VET) in 2018, were screened for K. pneumoniae by culturing on SCAI agar. K. pneumoniae was detected in 207 (40.5%) samples. Among the broiler samples, 25.8% were positive for K. pneumoniae, in contrast to turkey with 74.2% positive samples (p < 0.01). Antibiotic susceptibility testing was performed, in addition to investigating biofilm production. Whole genome sequencing was performed on 203 of the 207 K. pneumoniae-positive samples, and analysis was performed utilizing comparative genomics tools. The genomes grouped into 66 sequence types (STs), with ST35, ST4710 and ST37 being the most prevalent at 13.8%, 7.4% and 5.4%, respectively. The overall AMR occurrence was low, with only 11.3% of the isolates showing both pheno- and genotypic resistance. Genes encoding aerobactin, salmochelin or yersiniabactin were detected in 47 (23.2%) genomes. Fifteen hypervirulent genomes belonging to ST4710 and isolated from turkey were identified. These all encoded the siderophore virulence loci iuc5 and iro5 on an IncF plasmid. Isolates from both poultry species displayed good biofilm-forming abilities with an average of OD595 0.69 and 0.64. To conclude, the occurrence of K. pneumoniae in turkey was significantly higher than in broiler, indicating that turkey might be an important zoonotic reservoir for K. pneumoniae compared to broilers. Furthermore, our results show a highly diverse K. pneumoniae population in poultry, low levels of antimicrobial resistance, good biofilm-forming abilities and a novel hypervirulent ST4710 clone circulating in the turkey population.